2011
DOI: 10.1007/s00068-011-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple blunt trauma after suicidal attempt: an analysis of 4,754 multiple severely injured patients

Abstract: Falls from a height are a common cause of injury among severely injured patients. The resulting trauma composes a particular form of blunt trauma with severe and multiple injuries, which depends on the fact of whether the free fall from a height was caused by an accident or as a result of a suicidal attempt. Taking the injury severity into consideration, there is no difference in the prognosis of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Several previous studies have compared accidental and suicidal falls. [8][9][10][11] In these reports, relative to accidental falls, suicidal falls were more likely to occur in younger female patients, and injury patterns appeared to differ between groups. However, whether suicidal intent is associated with poor outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Several previous studies have compared accidental and suicidal falls. [8][9][10][11] In these reports, relative to accidental falls, suicidal falls were more likely to occur in younger female patients, and injury patterns appeared to differ between groups. However, whether suicidal intent is associated with poor outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 72%
“…Detailed examination of the differences in outcomes according to fall height are warranted, as low-level falls are sometimes associated with mortality. 15 Topp et al 10 demonstrated that while suicidal fall patients sus-tained severe injuries, which determined their outcomes, there was no difference in prognoses between patient groups with comparable injury severity. Nevertheless, suicide intent and injury severity were both risk factors for mortality in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Suicide attempts often cause severe injuries when compared to unintentional injuries and associated with increased hospital length of stay (HLOS), hospital cost as well as in-hospital mortality. [ 10 11 12 ] The present study aimed to determine the frequency of various methods of suicide, injury characteristics, and outcomes by gender of patients admitted to a level 1 trauma center in Qatar following suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…In PT patients, severe injuries of the thorax are regularly observed. At least 53.2% of the PT patients after a fall from a height [ 2 ], 42.8% of the pedestrians, and 60.1% of the motor vehicle occupants with a blunt trauma [ 3 ] presented with a severe injury of the thorax with an Abbreviated Injury Scale (AIS) [ 4 ] ≥ 3. Osseous injuries of the thorax are associated with a high level of pain [ 5 ] and, potentially, with a longer hospital stay and a prolonged invasive ventilation, especially when associated with sternal fractures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%